PEMBUATAN MINYAK KELAPA SECARA ENZIMATIS DENGAN MEMANFAATKAN KULIT BUAH DAN BIJI PEPAYA SERTA ANALISIS SIFAT FISIKOKIMIANYA - Nuzul Wahyuning Diyah; Purwanto; Yunita Susanti; Yuliana Kristiani Dewi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Enzymatic process using papain is an efficient and less expensive method for producing coconut oil. This research was conducted to produce coconut oil which meet quality requirement from Cocos Nucifera L using ripe fruit peel and seed of papaya (Carica Papaya L) as enzyme sources. The coconut oil was prepared by mixing of coconut milk and juice of papaya ripe fruit peel and/or seed; and then the oils produced and incubated for 24 hours. The physicochemical properties of the coconut oil were determined including specific gravity, water content, contaminant, Iodine number, saponification number, peroxyde number, acid number, and pelican oil. The yields of coconut oil produced by enzymatic method using those two papain sources were significantly higher than coconut oil produced by vaporization/heating method. The physicochemical properties of the coconut oil in accordance with Indonesian National Standard (SNI), but the coconut oil which was produced enzymatically using juice of papaya ripe fruit peel and seed had higher quality than those produced by heating method. Based on the physicochemical properties of the coconut oil, it concluded that ripe fruit peel of papaya was better than papaya seed as an enzyme source.